2016
DOI: 10.1016/j.jalz.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The DIAN‐TU Next Generation Alzheimer's prevention trial: Adaptive design and disease progression model

Abstract: INTRODUCTION The Dominantly Inherited Alzheimer Network Trials Unit (DIAN-TU) trial is an adaptive platform trial testing multiple drugs to slow or prevent the progression of Alzheimer’s disease in autosomal dominant Alzheimer’s disease (ADAD) families. With completion of enrollment of the first two drug arms, the DIAN-TU now plans to add new drugs to the platform, designated as the Next Generation Prevention Trial (NexGen). METHODS In collaboration with ADAD families, philanthropic organizations, academic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
262
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 239 publications
(281 citation statements)
references
References 65 publications
3
262
0
1
Order By: Relevance
“…Preventive clinical trials on presymptomatic carriers of highly penetrant variants of APP , PSEN1 , or PSEN2 belonging to EOAD families are currently ongoing (e.g., DIAN-TU). The study of such presymptomatic individuals indeed revealed that disease mechanisms, including Aβ aggregation, begin years before the clinical onset [116] . The prevention of Aβ aggregation or toxicity is therefore a promising solution to delay AD onset or prevent the disease in these very rare families.…”
Section: Resultsmentioning
confidence: 98%
“…Preventive clinical trials on presymptomatic carriers of highly penetrant variants of APP , PSEN1 , or PSEN2 belonging to EOAD families are currently ongoing (e.g., DIAN-TU). The study of such presymptomatic individuals indeed revealed that disease mechanisms, including Aβ aggregation, begin years before the clinical onset [116] . The prevention of Aβ aggregation or toxicity is therefore a promising solution to delay AD onset or prevent the disease in these very rare families.…”
Section: Resultsmentioning
confidence: 98%
“…With respect to preventive therapies, two clinical trialsthe DIAN-TU (Dominantly Inherited Alzheimer Network Trial Unit) and API (Alzheimer's Prevention Initiative)-are ongoing to test the efficacy of passive immunotherapy among normal or mildly symptomatic FAD mutation carriers. 5,6 Thus, it is important to enhance local doctors' knowledge of FAD.…”
Section: Resultsmentioning
confidence: 99%
“…Asymptomatic carriers are also potentially valuable for future clinical trials. [4][5][6] In terms of cognitive symptoms, patients with FAD tended to present slightly less frequently with amnesia than those with LOAD, although amnesia remained their main presenting cognitive symptom. This is in agreement with previous studies that reported EOAD patients to have more prominent frontoparietal dysfunction than medial temporal dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…These unfortunate 0.5 million people in 517 families in the world are destined for developing Alzheimer at the early age of 22-55, at about the same age as their mother or father, and their mother or father. The exact timing of dementia onset is dictated by the particular mutation in the APP, PS1 or PS2 gene [85][86][87][88]. To me, the DIAN people are the best 'human model' to study and understand the mind and what the brain does as time goes by, to uncover the molecular details and cellular mechanisms at work in the mind and body many decades before Alzheimer begins.…”
Section: Prevention Is the Only Curementioning
confidence: 99%